Analisis faktor-faktor penyebab kegagalan JPKM berdasarkan sikap peserta dan mantan peserta: studi kasus di Kabupaten Sleman = Analysis of factors for managed care failure based on the participants and exparticipants .. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Background: Managed care should be one of the basic components of every health system and the healthy vision/paradigm. Managed care is getting more important in the globalization era that demands public reliance. Nevertheless, the coverage of managed care in Indonesia is very low. In Sleman regency, the coverage was under 10.2 % in 1998, 3.49 % in 1999, which suggests that it dropped 65.78 %, and it was 1.3 % in 2000 (dropped 63/1 %). Objective: This study was aimed to explore society's attitude toward managed care components in order to find out weaknesses and influencing factors and their contribution toward failure of managed care. Method: The method of the study was cross sectional survey. The sample of the study was 259 people (48 of them were participants of managed care, 48 of them were ex-participants, and 163 of them were participants of social safety net of health/ SSNH) that were collected by multi-stage proportionate random sampling. Result: Alpha reliability coefficient of questionnaire was 0.9633.Validity testing showed that 83.72 % of items were very valid, 5.8 % were valid and 10.5 % were not valid (p0,05). The average score of participants, ex-participants and SSNH participants attitude toward prepaid payment system (PPS) were 3.45, 3.08 and 2.68 respectively(p = 0.00)